Profile and Determinants of Compounding Services among Pharmacists in Indonesia - Kristina, Susi Ari (Asian Journal of Pharmaceutics (AJP), 2018)
Introduction: Compounding practice in pharmacy is common, especially in the developing countries. However, the practice of compounding has not been well standardized, as it may lead to cross-contamination or low-quality products. Compounding practice may be influenced by many factors such as patient, health system, and economic issues. The purpose of this study was to determine the extent of compounding practice by pharmacists and to explore factors that influence pharmacists’ reasons to provide compounding services. Materials and Methods: The study was a cross-sectional survey using a self-administered questionnaire. Participants were pharmacists in charge in Yogyakarta Province area, working at pharmacies, hospitals, or clinics which provide pharmacy services. An anonymous questionnaire was sent door to door in practice sites. Data were analyzed descriptively. Findings: Among the 425 pharmacists who were contacted, 305 agreed to participate in the survey, giving a response rate of 71%. Overall, 286 (94.08%) pharmacists provided compounding services. Compounded prescriptions accounted for 155 (11.55%) of the 1342 total prescriptions dispensed per month. About 265 (40.4%) pharmacists reported that their aim to provide full pharmaceutical care to patients was one of the most important reasons for providing compounding service. About one-third of compounded prescriptions, 208 (30.1%), were general practitioners, while the remaining were specialized physicians. The three most commonly prescribed dosage forms were powder (32.1%), capsule (25.3%), and syrup (21.9%). The most frequent drug compounded was paracetamol (28.1%), chlorpheniramine maleate (11.4%), and ambroxol (10.6%). Regarding the pharmacists’ perception to control the quality of compounded products, most of the pharmacists answered that they feel confident in the quality of compounding because of the guideline provided (80.26%), documenting all procedure in compounding (73%), and the availability of special room for compounding (56.58%). Conclusion: Compounding service remains a core component of pharmacy practice. There is a need to develop evidence-based regulations for compounding practice by pharmacists.